Against all odds: how a government's open source software (OSS) implementation survived - Bahri, S.; Jaafar, N.I. (2014)
In this study, we suggest that actors and their relationship in an information systems (IS) implementation influence the survival of a government's open source software (OSS) project. Specifically, we investigated the OSS implementation by the Malaysian government since 2002. Due to the numerous and enormous challenges faced by such implementation such as inertia and concern about the quality of the software, the odds are often stacked against such project to survive. The theoretical lens of this study was the Actor-Network Theory (ANT) while the case study research method was employed to identify the actors and their relationships in ensuring the survivability of the project. Our findings suggest that the survival of the project was strongly influenced by the network built by its human and non-human actors that led to the successful enrolment and translation of the implementation. Furthermore, the actors can be divided into main and supporting with each contributing uniquely to the government's OSS implementation.